Clinical and epidemiological characteristics of head pediculosis in children. A retrospective study - G. A. Kharchenko; O. G. Kimirilova (Лечащий Врач, 2022)
In the structure of parasitic dermatoses, pediculosis is a common disease caused by various types of lice (head, pubic, dress) as a result of direct contact, through personal belongings, when using someone else's underwear, etc. and represents an epidemiological danger in terms of the spread of typhus and recurrent typhus. The purpose of the study. To assess the epidemiological situation of head pediculosis and to establish the frequency of occurrence of the main symptoms of the disease in children in the Astrakhan region (AO). Material and methods of research: the sources of information were the official data of Rospotrebnadzor JSC on pediculosis, for the period from 2013 to 2020 and 162 case histories of patients treated for infectious diseases in the State Medical Institution of JSC «Regional Infectious Clinical Hospital named after A.M. Nichogi» Astrakhan. Extensive (%) and intensive indicators per 100 thousand children under the age of 17 were used to establish the dynamics of the incidence of pediculosis. The results of the study: It was found that the epidemic process of the spread of pediculosis in children in AO, in the period from 2013 to 2020, exceeds the average in Russia with a tendency to decrease only in 2020. The most significant risk group for the spread of pediculosis were children aged 7 to 14 years. The main signs that make it possible to establish the presence of head pediculosis were: itching of the scalp, the presence of nits, detection of lice. Other signs of infectability with pediculosis (wet erosions, serous hemorrhagic crusts, papular urticaria, etc.) occurred with varying frequency, depending on the age of the child, and were of secondary importance, since they can occur with a number of other diseases (atopic dermatitis, seborrheic eczema, psoriasis, etc.). The detection of head pediculosis in organized preschool and school-age children, during hospitalization in hospitals, may indicate a formal approach to examination for pediculosis in preschool and educational institutions attended by a child.